Efeitos dos polissacarídeos sulfatados da alga marinha verde Caulerpa mexicana Sonder ex Kützing na nocicepção e inflamação - Carneiro, José Gerardo (2012)
Sulfated polysaccharides from seaweed are heterogeneous polymers representing biomolecules of commercial interest, especially in food and pharmaceutical industries. The aim this study was to evaluate the effects of total sulfated polysaccharides (TSP) of the green seaweed Caulerpa mexicana in classical models of nociception and acute inflammation in animals. Swiss male mice (18-25 g) and male Wistar rats (120-260 g) were used. The yield of the extraction of TSP obtained by enzymatic digestion was 1.7%. In analysis by Fourier transformed infrared were characterized as polysaccharides containing mainly sulfated galactose and uronic acid. The TSP of the alga C. mexicana were able to decrease (p <0.05) the number of writhes induced by acetic acid (1%) on 31.8, 74.5 and 88.9% at doses of 5, 10 and 20 mg/kg; i.v., respectively. In the formalin test, the TSP inhibited (p <0.05) the licking time of the paw only on the second of the test phase (88.6 and 98.5% for the doses 10 and 20 mg/kg; i.v., respectively). In the hot plate test, the TSP did not show antinociceptive effect in the course of 90 minutes of the test. Thus, the results suggest that the TSP presented analgesic effect by a peripheral action. In addition, TSP (5, 10 and 20 mg/kg) showed anti-inflammatory effect when administered s.c. in rats on paw edema models induced by carrageenan, dextran or histamine. To analyze the involvement of heme oxygenase (HO) pathway in the anti-inflammatory effect of TSP (20 mg/kg, sc), the animals were pretreated (s.c.) with a specific HO inhibitor (zinc protoporphirin IX). The results showed that the TSP were able to reduce the paw edema induced by carrageenan in the third hour, which was confirmed by myeloperoxidase quantification. In addition, the TSP reduced the edema induced by dextran or histamine in paw edema models in the first thirty minutes after application the flogistic agents. The anti-inflammatory effect of TSP on paw edema induced by carrageenan was not observed after prior inhibition by zinc protoporphyrin IX. Therefore, we suggest that the anti-inflammatory effect of TSP of the alga C. mexicana algae may be related to inhibition of the histamine release, reduction of cell migration and activation of the HO pathway. To evaluate the systemic effects of TSP, they were administered (i.v.) in mice (20 mg/kg) in a single-dose and evaluated the systemic changes for 48 h. The results showed that the TSP did not cause mortality or significant alterations on organs and on biochemical parameters being considered safe in the tested dose. In summary, the TSP from the algae C. mexicana have showed significant antinociceptive and anti-inflammatory effects, becoming an important biotechnological tool for further studies.